2017
DOI: 10.1371/journal.pone.0170572
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression in Xenopus Oocytes and Unusual Functional Properties of α1β2γ2 GABAA Receptors with Non-Conventional Subunit Arrangement

Abstract: The major subunit isoform of GABAA receptors is α1β2γ2. The subunits are thought to surround an ion pore with the counterclockwise arrangement α1γ2β2α1β2 as seen from the outside of the neuron. These receptors have two agonist sites and one high affinity drug binding site specific for benzodiazepines. Recently, this receptor was postulated to assume alternative subunit stoichiometries and arrangements resulting in only one agonist site and one or even two sites for benzodiazepines. In order to force a defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This was not reported originally, although careful examination of the data in Baumann et al (2001) reveals low levels of dimer-only expression. Later publications from the Sigel group also note the existence of functional receptors from expression of dimeric constructs by themselves (Kaur et al, 2009; Sigel et al, 2009; Baur and Sigel, 2017). Nevertheless, the key point is that dimers from both constructs assembled readily into fully functional receptors, likely with dangling subunits (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This was not reported originally, although careful examination of the data in Baumann et al (2001) reveals low levels of dimer-only expression. Later publications from the Sigel group also note the existence of functional receptors from expression of dimeric constructs by themselves (Kaur et al, 2009; Sigel et al, 2009; Baur and Sigel, 2017). Nevertheless, the key point is that dimers from both constructs assembled readily into fully functional receptors, likely with dangling subunits (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here we employed a ratio of 1:1:4 to minimise the occurrence of diheteromeric receptors. On the other hand, it has been shown that overexpression of γ2 subunits may result in an increased occurrence of receptors containing two γ2 subunits (Quirk et al, 1994 ; Benke et al, 1996 ; Botzolakis et al, 2016 ; Baur and Sigel, 2017 ). Incorporation of a second γ2 subunit (to produce α1γ2α1γ2β2 receptors) has been shown to cause a dramatic slowing in the GABAergic current deactivation rate relative to both the standard diheteromeric and triheteromeric GABA A R isoforms (i.e., α1β2α1β2β2 or α1β2α1γ2β2 receptors; Botzolakis et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%